Six‐dimensional quantitative DCE MR Multitasking of the entire abdomen: Method and application to pancreatic ductal adenocarcinoma. Issue 2 (21st January 2020) - Wang, Nan; Gaddam, Srinivas; Wang, Lixia; Xie, Yibin; Fan, Zhaoyang; Yang, Wensha; Tuli, Richard; Lo, Simon; Hendifar, Andrew; Pandol, Stephen; Christodoulou, Anthony G.; Li, Debiao
Abstract : Purpose: To develop a quantitative DCE MRI technique enabling entire‐abdomen coverage, free‐breathing acquisition, 1‐second temporal resolution, and T1 ‐based quantification of contrast agent concentration and kinetic modeling for the characterization of pancreatic ductal adenocarcinoma (PDAC). Methods: Segmented FLASH readouts following saturation‐recovery preparation with randomized 3D Cartesian undersampling was used for incoherent data acquisition. MR Multitasking was used to reconstruct 6‐dimensional images with 3 spatial dimensions, 1 T1 recovery dimension for dynamic T1 quantification, 1 respiratory dimension to resolve respiratory motion, and 1 DCE time dimension to capture the contrast kinetics. Sixteen healthy subjects and 14 patients with pathologically confirmed PDAC were recruited for the in vivo studies, and kinetic parameters vp, K trans, ve, and Kep were evaluated for each subject. Intersession repeatability of Multitasking DCE was assessed in 8 repeat healthy subjects. One‐way unbalanced analysis of variance was performed between control and patient groups. Results: In vivo studies demonstrated that vp, K trans, and Kep of PDAC were significantly lower compared with nontumoral regions in the patient group ( P = .002, .003, .004, respectively) and normal pancreas in the control group ( P = .011, <.001, <.001, respectively), while ve was significantly higher than nontumoral regions ( P < .001) and healthy pancreas ( P < .001). The kinetic parameters showed good in vivo repeatability (interclass correlation coefficient: vp, 0.95; K trans, 0.98; ve, 0.96; Kep, 0.99). Conclusion: The proposed Multitasking DCE is promising for the quantification of vascular properties of PDAC. Quantitative DCE parameters were repeatable in vivo and showed significant differences between normal pancreas and both tumor and nontumoral regions in patients with PDAC.